Colorimetric properties and commercial opportunity of pomegranate kernels (Punica granatum L.) under a minimum processing - Coret A.; Salazar D.; García E.; Melgarejo P. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
In this work, the tasting and microbiological quality of a new product based on pomegranate kernels has been studied when packed in semi-permeable plastic packing. The role and influence of the packaging conditions in the colorimetric and physico-chemical properties has been studied in depth in order to determine its influence on the quality of the product. It is concluded that the use of a modified atmosphere (93 per cent N2, 5 per cent CO2 and 2 per cent O2) combined with the use of potassium sorbate in acid conditions, or natural lemon juice leads to the product with the best tasting and colorimetric properties. This product has a higher luminosity and a lower yellow colour than other products tested and controlled.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)